2015
DOI: 10.1111/jbi.12658
|View full text |Cite
|
Sign up to set email alerts
|

Dated phylogenies and historical biogeography of Dontostemon and Clausia (Brassicaceae) mirror the palaeogeographical history of the Eurasian steppe

Abstract: Aim We hypothesize that molecular signals in Eurasian steppe plants reflect their biogeographical history as well as the climate/landscape history of the Eurasian steppe. To test this hypothesis we focus here on the characteristic Eurasian steppe genera Dontostemon and Clausia (Brassicaceae), and have included all presently accepted species in our study. Location Eurasian steppe from eastern Asia to south‐eastern Europe. Methods To elucidate their phylogeny, we sequenced the nuclear ribosomal ITS and chloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Hohmann et al (2015) estimated the emergence of clade E tribes at 17 mya, and the same estimate (17.2 mya) for the most recent common ancestor of clade E was reported by Huang et al (2016). A Middle Miocene divergence (15 mya) also was proposed for the basal split within DONT (between Clausia and Dontostemon; Friesen et al, 2016). Because the vast majority of Aethionemeae, a sister clade to all other Brassicaceae clades, occurs in the Irano-Turanian region (predominantly in Turkey) and one of the main diversity hotspots of the family is located there as well, this region is often referred to as the cradle of the family (Hedge, 1976;Franzke et al, 2009Franzke et al, , 2011; Couvreur Figure 3.…”
Section: Oligocene Origin and Miocene Diversification Of The Hesperismentioning
confidence: 78%
“…Hohmann et al (2015) estimated the emergence of clade E tribes at 17 mya, and the same estimate (17.2 mya) for the most recent common ancestor of clade E was reported by Huang et al (2016). A Middle Miocene divergence (15 mya) also was proposed for the basal split within DONT (between Clausia and Dontostemon; Friesen et al, 2016). Because the vast majority of Aethionemeae, a sister clade to all other Brassicaceae clades, occurs in the Irano-Turanian region (predominantly in Turkey) and one of the main diversity hotspots of the family is located there as well, this region is often referred to as the cradle of the family (Hedge, 1976;Franzke et al, 2009Franzke et al, , 2011; Couvreur Figure 3.…”
Section: Oligocene Origin and Miocene Diversification Of The Hesperismentioning
confidence: 78%
“…The Eurasian steppe belt was under strong influence of the Pleistocene glaciations that caused extensive expansions and contractions as well as latitudinal shifts and longitudinal splits of the ranges of steppe plant species during the past 3 million years (Hurka et al., 2019 and references therein). It has been shown that such a biome dynamic is mirrored by molecular signals of typical Eurasian steppe plants (e.g., Capsella orientalis ) and thus reflects their biogeographical history (Buono et al., 2021 ; Franzke et al., 2004 ; Friesen et al., 2016 , 2020 ; Hantemirova et al., 2020 ; Hurka et al., 2012 ; Seidl et al., 2019 , 2021 ; Seregin et al., 2015 ; Volkova et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…During this time the typical steppe habitats of the sect. Hymenostegis species were repeatedly shrinking and expanding due to the Pleistocene climate cycles, resulting in a constant shift between humid times, characterized by expanding forests, and dry periods where the steppes expanded again 4851 . It was already shown that these climate cycles could drive diversification in plant species through repeated subdivisions of populations resulting in allopatric speciation followed by range expansion when climate conditions became again favorable 44,5255 .…”
Section: Discussionmentioning
confidence: 99%